MEMBANGUN MINAT BEKOPERASI BAGI KAUM MILENIAL MELALUI DIGITAL MARKETING - Kresna Wirawan, I Dewa Gede; Firmani, Putu Siti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023, 2023)
The problem in this study is that cooperatives are increasingly facing difficulties along with their development in the era of globalization. Due to very rapid advances in information technology, robotics, artificial intelligence, transportation, and communication, the lifestyle of the millennial generation is changing in a disruptive way. This study uses library research techniques (library research). The secondary data currently being evaluated comes from a variety of sources, including books and journal papers. And so far cooperatives have received official support, based on their place in the Indonesian economic system. The findings of this study indicate that advances in technology, information and culture as well as shifts in people's attitudes and behavior should not be a threat to cooperatives but instead present opportunities. For this reason, cooperatives must take advantage of these advances, especially through the use of digital marketing, because this will increase their ability to contribute to the nation's economic growth in the industrial revolution.